PRIMARY INTRODUCTION RESULTS OF THE GENUS DACTYLORHIZA NECKER EX NEVSKI IN THE ALTAI BOTANICAL GARDEN (Experimental biology, 2021)
The primary introduction resulted in a stable collection of 4 species of the genus Dactylorhiza: D. fuchsii (Druce) Soo, D. incarnata (L.) Soo, D. maculata (L.) Soo, D. umbrosa (Kar. & Kir.) Nevski. Individuals of D. incarnata showed plasticity and good adaptability to conditions of culture. Their morphometric indicators of the length of the inflorescence increased by 14%, and the number of flowers in the inflorescence by 52%, indicators of the length and width of the basal leaves by 108% and 23% respectively. The results of the study have of great importance for the development of introduction agricultural technology of rare and endangered plants in the mountain taiga zone of East Kazakhstan, contribute to the preservation of biodiversity. Due to the short-term observation, more detailed analyzes of the results will be obtained with the further continuation of the introduction experiment.